Altered Processing of Social Emotions in Individuals With Autistic Traits - Yang, Di; Tao, Hengheng; Ge, Hongxin; Li, Zuoshan; Hu, Yuanyan; Meng, Jing (Frontiers in Psychology, 2022)
Social impairment is a defining phenotypic feature of autism. The present study investigated whether individuals with autistic traits exhibit altered perceptions of social emotions. Two groups of participants (High-AQ and Low-AQ) were recruited based on their scores on the autism-spectrum quotient (AQ). Their behavioral responses and event-related potentials (ERP) elicited by social and nonsocial stimuli with positive, negative, and neutral emotional valence were compared in two experiments. In Experiment 1, participants were instructed to view social-emotional and nonsocial-emotional pictures. In Experiment 2, participants were instructed to listen to social-emotional and nonsocial-emotional audio recordings. More negative emotional reactions and smaller amplitudes of late ERP components (the late positive potential in Experiment 1 and the late negative component in Experiment 2) were found in the High-AQ group than in the Low-AQ group in response to the social-negative stimuli. In addition, amplitudes of these late ERP components in both experiments elicited in response to social-negative stimuli were correlated with the AQ scores of the High-AQ group. These results suggest that individuals with autistic traits have altered emotional processing of social-negative emotions.